The Influence of Economic Conditions and Psychological Conditions of the Community on Government Readiness in the Development of the National Capital - Arwin Sanjaya; Sitti Hardiyanti Arhas; Setya Maulana Pratama; I Ketut Gunawan (Jurnal Ad'ministrare, 2022)
The determination to move the capital city to Eastern Indonesia is expected to reduce inequality and realize sustainable development in Indonesia, as well as create a new capital city that is in accordance with the nation's identity. This study aims to determine the effect of the economic condition and the psychological condition of the community on the government's readiness in the development of the National Capital City (IKN). To achieve the research objectives used associative quantitative research. The population in this research is the people on the island of Kalimantan. The selected sample is 100 respondents. Analysis of the data used is multiple linear regression analysis. The results showed that simultaneously the economic and psychological conditions of the community had a positive and significant effect on the government's readiness to develop IKN. Meanwhile, simultaneously only economic conditions have a positive and significant impact on the government's readiness to develop IKN. This research is a new thing with a new discussion that relates the economic condition and the psychological condition of the community, especially regarding what is currently a trending topic in the community, namely the development of the nation's capital city.